Pengamalan Sifat Pemaaf Perspektif Wahbah Az-Zuhaili dalam Tafsir Al-Munir - Muhammad Labib Alfayyadh; Sohib Syayfi (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This research article examines the concept of practicing forgiveness as interpreted in Tafsir Al-Munir by Wahbah Az-Zuhaili, focusing specifically on Surah Al-A’raf verse 199 and Surah An-Nur verse 22. The study employs a thematic method with a descriptive qualitative approach, concentrating on an analysis of Wahbah Az-Zuhaili's Tafsir Al-Munir through library research to understand the interpretation related to specific themes within the Qur'an. The primary source is Tafsir Al-Munir, while secondary sources include relevant articles and online resources (websites) discussing the related topic. This matter of forgiveness needs to be examined to deepen the knowledge thereof, especially concerning its implementation in real life. The research findings indicate that Wahbah Az-Zuhaili categorizes the forgiveness mentioned in Surah Al-A’raf verse 199 as part of the fundamental social ethics encompassing tolerance, gentleness, and ease in interactions without burdening others. In Surah An-Nur verse 22, he emphasizes the importance of forgiving without retaliation, restoring social relationships, and demonstrating kindness, as exemplified by Abu Bakr towards Misthah. Furthermore, forgiveness must be performed with sincerity as a manifestation of faith, seeking mercy and pardon from Allah, without expecting reward from humans.